Jurisprudential Controls for the Use of Artificial Intelligence: A Practical Study of "Chat GPT" as a Model - ALafaghani, Falasteen Farag (Dirasat: Shari'a and Law Sciences, 2025)
Objectives: The study aims to clarify the reality of "Chat GPT" technology, its operational nature, and the general jurisprudential controls for its use. It also explores the jurisprudential controls specific to the "content," "user," "developers," and "programmers," while testing the validity and accuracy of its data in fields such as Fatwa issuance, translation of Sharia texts, and Hadith sciences. A practical applied test was conducted to evaluate this technology and validate the study’s findings. Methods: The study utilized inductive, analytical, and applied approaches by inducting the scientific material, analyzing it, and conducting a practical applied test in selected areas of Sharia sciences. Results: The study found that a balanced approach, considering both benefits and harms, is essential for the use of this technology. It concluded that fatwas should not be taken from "Chat GPT," as it does not meet the necessary conditions for a Mufti. The translation of Sharia texts lacks the jurisprudential depth required, and weaknesses were identified in the knowledge and understanding of the system, particularly in Hadith sciences regarding narrations and chains of transmission. Conclusions: The invention of a technology like “Chat GPT” is important, but its development should follow Sharia principles and recognized guidelines. This would allow Muslim youth to use the technology in a manner consistent with Sharia controls.